PEMERIKSAAN PERTUMBUHAN BADAN SISWA SEKOLAH DASAR (SD) DENGAN MENGGUNAKAN METODE ANTROPOMETRI DI DESA ERETAN WETAN-INDRAMAYU - Yovita Harmiatun; Fri Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2020)
Abstract Growth is an increase in the physical size of the body indicated by an increase in the frequency and volume of cells as a whole or in part that can be measured. Many factors influence body growth, one of which is environmental factors. Environmental factors are the most common and can be modified is food. Food as a source of nutrients and building substances in the body. Imbalanced nutrition can cause various health problems. Pengabdian kepada mayarakat (PkM) which aims to see the nutritional status of the growth of “X” and 'Y ”Elementary School students in Indramayu in a series of PKM activities at the Faculty of Medicine-Indonesian Christian University in Eretan Wetan Village, Kandanghaur -Indramayu on February 22, 2020. The method used is the anthropometric method, namely the measurement of body weight and height, then from the measurement results the value of the Body Mass Index (BMI) is calculated. Based on the BMI value obtained, it is known that out of 245 students, it was found that 60 students (24.5%) had a problematic nutritional status, namely experiencing thinness and obesity. Among students with problematic nutritional status, it was found that 46 students (76.6%) were classified as thin and 14 students (23.3%) were classified as fat. Therefore, it is necessary to identify the types and varieties of food consumed by the SD